Kolmogorov widths and entropy numbers in the Orlich spaces with the Luxembourg norm - Romanyuk, V. S. (Ukrains’kyi Matematychnyi Zhurnal, 2017)
We obtain the exact-order estimates of the Kolmogorov widths and entropy numbers of unit balls from the binary Besov spaces $dyad B^0,γ_ p,θ compactly embedded in the exponential Orlich exp L^ u spaces equipped with the Luxembourg norm.